2022
DOI: 10.3390/buildings13010037
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength Models for Reinforced Concrete Slender Beams: Comparative Analysis and Parametric Evaluation

Abstract: Shear failure of reinforced concrete (RC) members belongs to brittle failure and has always been concerned. In this paper, 16 existing shear strength models of RC slender beams have been selected and comprehensively compared based on a set of 781 experimental test results. These formulas from eight national codes and eight published papers are mainly the semi-empirical models or the analytical models. These experimental test results were collected from 66 published papers, and the range of key parameters is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The "size effect in shear" is often defined in literature as the decrease in shear capacity of reinforced concrete beams with the increase in a member depth. Such definition was demonstrated in several papers [10][11][12][13][14][15][16][17][18][19]. To illustrate the size effect in shear, test results obtained by Bažant and Kazemi [11] are presented in Figure 2.…”
Section: Introductionmentioning
confidence: 77%
“…The "size effect in shear" is often defined in literature as the decrease in shear capacity of reinforced concrete beams with the increase in a member depth. Such definition was demonstrated in several papers [10][11][12][13][14][15][16][17][18][19]. To illustrate the size effect in shear, test results obtained by Bažant and Kazemi [11] are presented in Figure 2.…”
Section: Introductionmentioning
confidence: 77%
“…Moreover, the difference in the experimental and analytical shear strengths decreased with an increase in a/d ratio from 1.6 to 4.3. Ma et al [72] also reported a large difference in the experimental and analytical shear strengths of OPCCB specimens estimated using ACI 318-19 [40] and JSCE 2007 [43] at lower a/d ratios and the difference between experimental and analytical shear strengths were decreased with an increase in a/d ratio from 2.5 to 7.5. Buildings 2024, 14, x FOR PEER REVIEW 17 of 24…”
Section: Analytical Results and Discussionmentioning
confidence: 99%
“…The existing shear strength formulas of RC beams can be classified into five categories based on mechanisms and methodologies including; empirical models, semi-empirical models, mechanics-based approaches, probabilistic models and machine learning-based models (Ma et al, 2023). Zsutty (1968) developed empirical models that incorporated f c , ρ and a/d as parameters.…”
Section: Introductionmentioning
confidence: 99%